Strategi Komunitas Pejuang Subuh dalam Berdakwah dan menjaga Eksistensinya di Kota Jambi - M.Ridho; Zurqarnin; Ahdiyat Mahendra (MAUIZOH: Jurnal Ilmu Dakwah dan Komunikasi, 2021)
This research is motivated by the rapid development of the dawn warrior community so that it has mushroomed in almost all parts of Indonesia and has had tens of thousands of members, including Jambi, for more than 2 years the Jambi dawn warrior community has had thousands of members, of course it didn't just happen, it was all This study aims to determine the strategy of the Jambi dawn warrior community in preaching and maintaining its existence in Jambi City, and the effectiveness of the strategies used by the administrators. The research that the author uses is a qualitative research. The data collection techniques are interviews with 13 informants, observations from November 2020 to February 2021, and documentation. The results of the strategy research in preaching are: staying in touch with mosque administrators in Jambi City, making fun activities, creating good relationships with each member and using social media and other media as a means of developing da'wah. Strategies in maintaining the existence of the dawn warrior community are: making priority and non-priority programs, collaborating with various communities and organizations, da'i, and taklim assemblies in Jambi City, seeking and maintaining the trust of donors.